Pengaruh Tekanan Dan Tahap Kompresi Dalam Pemurnian Biogas Menjadi Biometana Dengan Absorpsi CO2 Menggunakan Air Bertekanan - Raksajati, Anggit; Adhi, Tri Partono; Ariono, Danu (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Palm oil mill effluent (POME) from condensate stew, hydrocyclone water, and sludge separator contains organic carbon with a COD more than 40 g/L and a nitrogen content of about 0.2 and 0.5 g/L as ammonia nitrogen and total nitrogen. At present, the POME is converted into biogas using anaerobic ponds. Biogas produced contains 60% methane (CH4) and 40% carbon dioxide (CO2) and can be purified into biomethane through CO2 absorption using water. This study evaluates the optimum pressure and feed compression stage in biogas upgrading into biomethane. The results show the rate of circulation of water needed to separate CO2 from biogas feed decreases with increasing absorber pressure due to increased solubility of CO2 in water. Water circulation pumps and biogas compressor works increase due to the increase in pressure difference needed. The optimum pressure of the biogas biogas purification unit is within the range of 7-10 bar. At the same absorber pressure, the 1 stage feed compression unit is cheaper than that of 2 stages. However, the overall process with 1 compression stage might not be more economical than the 2-stage if consider the higher methane loss.